Factors Associated with Teenage Pregnancies During the Covid-19 Period in Pakwach District, Northern Uganda: A Case-Control Study - Alunyo JP; Mukunya D; Napyo A; Matovu JK; Okia D; Wanume B; Okello F; Tuwa AH; Wenani D; Okibure A; Omara G; Olupot-Olupot P (Adolescent Health, Medicine and Therapeutics)
Jimmy Patrick Alunyo,1,2 David Mukunya,1 Agnes Napyo,3 Joseph KB Matovu,1 David Okia,1 Benon Wanume,1 Francis Okello,1 Ally Hassan Tuwa,1 Daniel Wenani,1 Ambrose Okibure,1 Godfrey Omara,1 Peter Olupot-Olupot1,2 1Department of Community and Public Health, Busitema University, Mbale, Uganda; 2Department of Research, Mbale Clinical Research Institute, Mbale, Uganda; 3Department of Nursing Science, Kabale University, Kabale, UgandaCorrespondence: Jimmy Patrick Alunyo, Email alunyo.j.patrick@gmail.comBackground: Teenage pregnancy rates have globally decreased over the years, but remain high, especially in low- and middle-income countries (LMICs). Among girls aged 15– 19, teenage pregnancy remains the leading cause of death and a significant barrier to education and productivity. Its prevalence was high in pakwach district as reported by the DHO and police report during the pandemic. However, limited data exist regarding factors contributing to its rise during the COVID-19 pandemic in Uganda. This study explores the factors associated with teenage pregnancy in Pakwach district during this period.Methods: We conducted a matched case-control study, enrolling 362 teenage girls aged 10– 19 years, divided into two groups: 181 pregnant teenagers and 181 non-pregnant teenagers. We collected exposure data from both groups using a questionnaire to assess factors associated with teenage pregnancy. The study period covered March 2020 to January 2021, coinciding with lockdown measures.Results: During the COVID-19 period, teenage pregnancies were only associated with having exclusively female peers (AOR 3.0, 95% CI: 0.1– 104.4). Conversely, having a Radio/TV at home (AOR 0.2, 95% CI: 0.1– 0.6), age at first sexual encounter (AOR 0.1, 95% CI: 0.03– 0.9), considering teenage pregnancy as sexual abuse (AOR 0.1, 95% CI: 0.02– 0.4), feeling comfortable asking questions during consultations (AOR 0.5, 95% CI: 0.2– 1.3), and ensuring sufficient privacy during consultations were protective against teenage pregnancy.Conclusion: The factors contributing to increased teenage pregnancies during the COVID-19 pandemic were consistent with long-standing contextual factors associated with teenage pregnancy. The lockdown environment may have slightly exacerbated these factors, but no direct association was observed. Only having female peers was linked to teenage pregnancy during the lockdown. But more importantly for our study population, having access to a radio/TV at home and other healthcare system-related factors were protective during the lockdown. Therefore, interventions should be focused on making pregnancy prevention information available to teenagers during any lockdown scenario.Keywords: a case-control study, healthcare providers, COVID-19, teenage pregnancy, outcomes